My first colours let's learn them all! - Davis, Sarah; Calver, Susan; Mehra, Nidhi; Palastanga, Victoria (London dorling kindersley, 2023)
"From bright red fire engines to a gorgeous rainbow, this is the perfect first colours book for toddlers to share with grown-ups. Colourful pictures and fun-filled questions get children thinking and talking. East-grip picture tabs invite little fingers to turn right to the pages they love!
Scientific notions
Keywords: Science